(untitled) (The Harvest, 2024)
Staphylococcus aureus, being an opportunistic pathogen, is frequently associated with various infections in human. The clinical sector feels challenge regarding the management of multidrug resistant S. aureus. Besides the B-lactam antibiotics, Glycopeptides, Tetracycline, Quinolones, Macrolide-lincosamide streptogramin B family of antibiotics are also commonly prescribed to deal with such infections as an alternative drug. Therefore, this study was conducted to assess tetracycline susceptibility in multidrug resistant S. aureus in clinical samples. This study was conducted over the period of 15 months from March 2020–May 2021. The clinical samples were collected from the three different tertiary care hospitals of Kathmandu, Dirghayu Guru Hospital, Chabahil, Bhaktapur Cancer Hospital, Bhaktapur, and Shankarapur Hospital, Jorpati. The sample processing and laboratory work was carried out in the Microbiology Laboratory of Dirghyau Guru Hospital to determine the proportion of different phenotypes of MDR among S. aureus and their association with methicillin resistance. Two hundred sixty six isolates of S. aureus were included in the study. Methicillin resistance was detected by cefoxitin disc diffusion method. Among 2004 clinical samples processed, 266 (13.27%) isolates were S. aureus. The multidrug resistant strain isolated from OPD was 56.84% (54/95) and from inpatient was 43.15% (41/95). Among the 266 S. aureus, 28.94% MRSA and 71.05% MSSA isolates were detected. Tetracycline resistance was found in 9.8% of total S. aureus isolates whereas 27.36% (26/95) among MDR S. aureus isolates. Resistance to Tetracycline was higher in MRSA as compared to MSSA. Detection rate of MRSA in this study shows the necessity to improve health care practices to control MRSA infections. Tetracycline can be used as an alternative antibiotic against the S. aureus infection.